Impact of service quality on customer satisfaction and customer loyalty: Evidence from banking sector - Mubbsher Munawar Khan; Mariam Fasih (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The aim of this research study is to determine the satisfaction level of banking customers regarding quality of different services provided by their bank and their loyalty with the respective bank. Service quality is studied within a spectrum of different dimensions. An effort is also made to find out which service quality dimensions may enhance customer satisfaction and customer loyalty in a better way. Respondents are chosen from a range of varying demographic features using stratified random sampling. Banks from both public and private sector are selected for sampling. Survey questionnaires were distributed among 270 customers of different banks. An 83% (225 respondents) valid response rate is yielded. Descriptive statistics, one sample t-test, correlation and regression are used to analyze the data. Findings indicate that service quality and all its dimensions have significant and positive association with customer satisfaction and customer loyalty. Banking sector is a significant sector in Pakistan's economy and has seen unprecedented growth and raging competition during the last decade. Therefore this study has been specifically conducted to look into this phenomenon and seek empirical justification in this regard by considering service quality as the main contributory factor towards customer satisfaction and customer loyalty.
Keywords: 330; banking sector; customer loyalty; customer satisfaction; service quality